Heterohelicenes with Embedded P‐Chiral 1H‐Phosphindole or Dibenzophosphole Units: Diastereoselective Photochemical Synthesis and Structural Characterization. Issue 30 (13th June 2013) - Yavari, Keihann; Retailleau, Pascal; Voituriez, Arnaud; Marinetti, Angela
Abstract The oxidative photocyclization reactions of olefins that contain 1H‐phosphindole or dibenzophosphole substituents have been applied to the synthesis of P/N‐bi‐heterosubstituted dimeric helicenes, as well as of new [6]‐ and [8]phosphahelicenes. In these photocyclization processes, the configuration of the stereogenic phosphorus center dictates the sense of helical chirality. Thus, by starting from enantiomerically pure P‐menthylphosphole‐oxide units, this method affords enantiopure helical compounds. The helical phosphine oxides were characterized by X‐ray diffraction. After reduction of the phosphine‐oxides, the corresponding helical phosphines have been used as ligands in transition‐metal complexes. The X‐ray crystal structure of a gold chloride complex of a [6]helicene is reported.